PAREIASAURIAN TRACKS FROM THE UPPER PERMIAN OF EASTERN EUROPE - Gubin Yu.M.; Golubev V.K.; Bulanov V.V.; Petuchov S.V. (My University, 2003)
The first footprints and tracks of large terrestrial reptiles were discovered in the Late Tatarian deposits in northem European Russia. The tracks were found in light gray thick-bedded limestone of the Upper Tatarian (Proelginia permiana Tetrapod Zone, Severodvinian Horizon, Upper Permian). The locality was formed on the shore of a large lake in the subhumid seasonal climate. Two tracks extending about two meters each are described in detail. These tracks belong to quadrupedal pentadactyl reptiles with a body length exceeding 1 m. The manus is elongated and turned medially, the first digit is positioned perpendicular to the axis of the animal's movement. The second digit of the forelimb is the longest. Pes imprints are subtriangular, the third digit is parallel to the movement axis, the longest pes digits are the second and third. We tentatively assign the tracks to large pareiasaurians of the family Bradysauridae with a glenoacetabular distance longer than 85 cm. A new ichnogenus and ichnospecies, Sukhonopus primus, are described.
Keywords: Permian; Paleozoic::Permian; Палеозой::Пермская